2009
DOI: 10.1111/j.1751-1097.2009.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Factors and Mechanisms Underlying the Improved Photodynamic Cell Killing with Silicon Phthalocyanine Photosensitizers Directed to Lysosomes Versus Mitochondria

Abstract: The phthalocyanine photosensitizer Pc 4 has been shown to bind preferentially to mitochondrial and endoplasmic reticulum membranes. Upon photoirradiation of Pc 4-loaded cells, membrane components, especially Bcl-2, are photodamaged and apoptosis, as indicated by activation of caspase-3 and cleavage of poly(ADP-ribose) polymerase, is triggered. A series of analogs of Pc 4 were synthesized, and the results demonstrate that Pcs with the aminopropylsiloxy ligand of Pc 4 or a similar one on one side of the Pc ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
79
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 25 publications
(29 reference statements)
8
79
0
Order By: Relevance
“…In a study involving a direct comparison, it was shown that lysosomal photodamage is much more phototoxic than photodamage directed at mitochondrial and ER targets. 15 Experimental data are consistent with lysosomal photodamage initially leading to a loss of the low lysosomal pH needed for the optimal activity of lysosomal proteases. 16 This can result in an accumulation of autophagosomes that are unable to progress further.…”
supporting
confidence: 72%
“…In a study involving a direct comparison, it was shown that lysosomal photodamage is much more phototoxic than photodamage directed at mitochondrial and ER targets. 15 Experimental data are consistent with lysosomal photodamage initially leading to a loss of the low lysosomal pH needed for the optimal activity of lysosomal proteases. 16 This can result in an accumulation of autophagosomes that are unable to progress further.…”
supporting
confidence: 72%
“…The equilibrium association constant of Pc 4 in the PCL core of the micelle is of the same order as that obtained for Pc 4 incorporated in liposomes. 35 It has also been reported that a zinc-phthalocyanine binds red blood cells with an association constant of (1.4 AE 0.3) Â 10 4 M À1 . 47 The difference in the order of magnitude between a zinc and a silicon phthalocyanine (1.7 Â 10 3 M À1 ) is possibly because of the difference in aggregation characteristics between the two compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In water, without polymer, the hydrophobic Pc 4 is highly aggregated and insoluble and hence shows minimum fluorescence. [35][36][37] Upon addition of polymer, Pc 4 becomes disaggregated and solubilized (by association with the PCL core of PEG-PCL micelles) which results in increased fluorescence intensity. The increase in fluorescence continues with progressive increase in polymer concentration until saturation when Pc 4 is in its maximum equilibrium association state with the hydrophobic PCL core of the micelles.…”
Section: Pc 4 Encapsulation and Determination Of Association Constantmentioning
confidence: 99%
“…31 The authors proposed that "other factors, such as different initial targets or different mechanisms of cell death, may also contribute to the observed differences in photodynamic efficiency." We propose that the photodynamic efficiency of lysosomal photosensitizers reflects their ability to disrupt the autophagic process.…”
Section: Subcellular Localization Of Photosensitizersmentioning
confidence: 99%